Struktura argumentacje we wniosku formalnym na wybranym przykładzie - Kamasa, Victoria (My University, 2012)
The aim of the paper is to reconstruct the argumentational structure of formal inquiry on chosen example. It also attempts to assess the validity of every identified part of argumentations. This assessment is done by the use of notions and methods postulated by Tokarz (2006) for formalization and judgment of argumentation. As a result, proposal of general structure of argumentation and structure of every subarguments used in analyzed text is presented.
The argumentation structure in formal inquiry choosen example